2014
DOI: 10.4314/ahs.v14i3.26
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and outcomes of acute kidney injury in term neonates with perinatal asphyxia

Abstract: Background: The kidney is the most damaged organ in asphyxiated full-term infants. The severity of its damage is correlated with the severity of neurological damage. We determined the prevalence of perinatal asphyxia-associated acute kidney injury (AKI). Methods: We conducted a prospective cohort study including 60 full-term neonates admitted at the Kenyatta National Hospital newborn unit (NBU) in Nairobi with hypoxic ischaemic encephalopathy (HIE) from June 2012 to November 2012. Renal function was assessed b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
51
3
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(63 citation statements)
references
References 11 publications
8
51
3
1
Order By: Relevance
“…Kaur et al [38] reported an AKI incidence of 41.7% in asphyxiated neonates, with an incidence of 9.1% in infants with moderate asphyxia and 56% among infants with severe asphyxia. Other studies support the correlation of AKI incidence with advancing severity of hypoxic ischemic encephalopathy [39,40] (Table 2). Newborns with congenital heart diseases affecting systemic circulation, and especially those undergoing cardiopulmonary bypass, also have higher incidences of AKI than the baseline neonatal population [41,42].…”
Section: Groups At High Risk Of Developing Aki In the Neonatal Periodsupporting
confidence: 59%
“…Kaur et al [38] reported an AKI incidence of 41.7% in asphyxiated neonates, with an incidence of 9.1% in infants with moderate asphyxia and 56% among infants with severe asphyxia. Other studies support the correlation of AKI incidence with advancing severity of hypoxic ischemic encephalopathy [39,40] (Table 2). Newborns with congenital heart diseases affecting systemic circulation, and especially those undergoing cardiopulmonary bypass, also have higher incidences of AKI than the baseline neonatal population [41,42].…”
Section: Groups At High Risk Of Developing Aki In the Neonatal Periodsupporting
confidence: 59%
“…Of these 260 study cases, 139 (53.5 %) were male patients while 121 (46.5 %) were female patients. A study conducted in Kenya by Alaro et al 12 has also reported 60 % male gender predominance which is close to our study results. A study conducted by Medani et al 13 from Sudan has also reported 59 % male gender predominance which is similar to that of our study results.…”
Section: Discussion;supporting
confidence: 92%
“…The incidence of asphyxia is estimated to be between 1 and 8 per 1000 live births. This wide range can be largely attributed to problems in selecting indicators to identify children with perinatal asphyxia 12,13 .…”
Section: Discussion;mentioning
confidence: 99%
“…After 24 h, the supernatant containing non-adherent cells was removed and fresh medium was added. The medium was changed every 3–5 days, after the cells had grown to near confluence and the density was approximately (4–5)×10 5 cells/cm 2 ; the cells were passaged 3 times and the suspended cells were discarded. Subsequently, the pure adherent cells (BMSCs) were cultivated for further analysis.…”
Section: Methodsmentioning
confidence: 99%